ANALISIS KELAYAKAN PEMBENIHAN UMBI BAWANG MERAH (Studi Kasus di Penangkar Benih Sentani Desa Kelompok Kecamatan Wanasari Kabupaten Brebes) - Muhammad Maftukin; Dewi Hastuti; Endah Subekti (MEDIAGRO, 2015)
Seed factors plays an important role in determining the success of crop production. The use of high quality seeds is the first step to increase production, so as to increase the income of farmers through the cultivation of onions. This study aims to determine the feasibility of onion bulbs seeding seen from BEP, NPV, IRR in Sentani Seed Breeder. location determination techniques using purposive, Data were collected by census techniques.The sample area is taken Klampok Village. The number of respondents of 20 people from Group Sentani Seed Breeder. the results showed of the average cost of investment Rp. 12,042,225, - with an average operating cost every production Rp. 15,575,721, - and the average revenue of Rp. 30,190,752, - / production while the average income of Rp. 14,615,031, - / production. The average number of respondents production amounted to 1,776 kg / production. On average BEP calculation production is 648 kg / production. This means that production has exceeded BEP. SOCC 19% level resulted in a positive NPV value of Rp. 36,288,145.27, - and IRR of 85.79%. Based those three analysis, the enterprise of onion bulbs seeding in Sentani Seed Breeder was feasible to be cultivated